Sick! diseases and disorders, injuries and infections - Newton, David E (Detroit : U X L, 2000)
Presents articles describing the causes and symptoms, diagnosis, treatment (both traditional and alternative), prognosis, and prevention of various diseases, disorders, injuries, and infections
v. 1. A-C -- v. 2. D-H -- v. 3. I-O -- v. 4. P-Z
Includes bibliographical references and indexes
Keywords: Health -- encyclopedias; Diseases -- encyclopedias